Conflict continues: Transitioning into a battle for property in Cambodia today. (22nd December 2015) - Kent, Alexandra
Abstract : This article discusses the ongoing hybrid war crimes tribunal taking place in Cambodia — in the Extraordinary Chambers in the Courts of Cambodia (ECCC) — in relation to the simultaneous eviction of the Boeung Kak Lake community in the capital, Phnom Penh. Presenting these two phenomena alongside one another highlights the contradiction inherent in the liberal peace model's humanitarian rhetoric of societal reconstruction and its economic imperatives, which serve the interests of the elites. The material discussed here suggests that so-called transitional justice interventions may accompany a period of stabilisation, which is good for the global market, but do little to enhance fairness and peace for ordinary people.